A survey of dental treatment under general anesthesia in a Korean university hospital pediatric dental clinic - Shin, Bisol (J Dent Anesth Pain Med, 2016)
BACKGROUND: In South Korea, the number of cases of dental treatment for the disabled is gradually increasing, primarily at regional dental clinics for the disabled. This study investigated pediatric patients at a treatment clinic for the disabled within a university hospital who received dental treatment under general anesthesia. This data could assist those that provide dental treatment for the disabled and guide future treatment directions and new policies. METHODS: This study was a retrospective analysis of 263 cases in which patients received dental treatment under general anesthesia from January 2011 to May 2016. The variables examined were gender, age, reason for anesthesia, type of disability, time under anesthesia, duration of treatment, type of procedure, treatment details, and annual trends in the use of general anesthesia. RESULTS: Among pediatric patients with disabilities who received dental treatment under general anesthesia, the most prevalent age group was 5–8 years old (124 patients, 47.1%), and the primary reason for administering anesthesia was dental anxiety or phobia. The mean time under anesthesia was 132.7 ± 77.6 min, and the mean duration of treatment was 101.9 ± 71.2 min. The most common type of treatment was restoration, accounting for 158 of the 380 treatments performed. CONCLUSIONS: Due to increasing demand, the number of cases of dental treatment performed under general anesthesia is expected to continue increasing, and it can be a useful method of treatment in patients with dental anxiety or phobia.